Answer:
[tex]B=7x^4[/tex]
Step-by-step explanation:
The given equality is
[tex]-35x^6=(-5x^2)B[/tex]
Take the term [tex](-5x^2)[/tex] to the left hand side. This means the term [tex]-35x^6[/tex] will be divided by [tex](-5x^2)[/tex]
[tex]\dfrac{-35x^6}{(-5x^2)}=B[/tex]
Now since both the numerator and denominator have negative sign the value of fraction will be positive.
[tex]\dfrac{35x^6}{(5x^2)}=B[/tex]
Now [tex]5\times 7=35[/tex] and [tex]x^{6-2}=x^4[/tex]
[tex]7x^4=B[/tex]
So, the missing factor [tex]B=7x^4[/tex]